2018
DOI: 10.1371/journal.pone.0189849
|View full text |Cite
|
Sign up to set email alerts
|

Testing the stress-buffering hypothesis of social support in couples coping with early-stage dementia

Abstract: PurposeTo test whether the negative relationship between perceived stress and quality of life (Hypothesis 1) can be buffered by perceived social support in patients with dementia as well as in caregivers individually (Hypothesis 2: actor effects) and across partners (Hypothesis 3: partner effects and actor-partner effects). MethodA total of 108 couples (N = 216 individuals) comprised of one individual with early-stage dementia and one caregiving partner were assessed at baseline and one month apart. Moderation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 58 publications
2
33
1
2
Order By: Relevance
“…Further, most studies showed comparable results investigating multidimensional associations of the QUALI-DEM subscales [25][26][27][28][29][30]. Moreover, in our study, we did not find significant outcomes regarding gender, age, FAST, and Barthel Index, which contradicts findings from the literature [42,43]. Thus, more research is needed to examine the association of momentary QoL and other indicators of health and functioning.…”
Section: Discussioncontrasting
confidence: 97%
“…Further, most studies showed comparable results investigating multidimensional associations of the QUALI-DEM subscales [25][26][27][28][29][30]. Moreover, in our study, we did not find significant outcomes regarding gender, age, FAST, and Barthel Index, which contradicts findings from the literature [42,43]. Thus, more research is needed to examine the association of momentary QoL and other indicators of health and functioning.…”
Section: Discussioncontrasting
confidence: 97%
“…12 This hypothesis has been tested in a wide range of studies and populations. 10,[13][14][15] However, no study of which we are aware has explored social support as a moderator of the association between stress and physical activity in rural cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Higher social support (especially from caregivers) has been found to be protective against mental health difficulties among ALHIV (Gentz et al, 2017) and for suicidal behaviours among youth in high-income countries; this includes evidence from longitudinal studies (McKinnon et al, 2016;Teismann et al, 2016). Social support can impact these psychological outcomes either by means of a direct effect, or by buffering the negative effects of specific stressors on these outcomes (Alloway and Bebbington, 1987;Casale et al, 2015a;Gellert et al, 2018). While multiple studies show direct protective effects of social support on depression and suicide among people living with HIV (Bitew et al, 2016;Brandt, 2009;Gentz et al, 2017), the evidence for stress-buffering is mixed: some studies have found social support to moderate effects of HIV-related stressors, such as financial stress or HIV-illness, on mental health outcomes (Robbins et al, 2003;Wight et al, 2003), while others did not find stressbuffering effects for HIV-related stigma (Breet et al, 2014;Rueda et al, 2012).…”
Section: Introductionmentioning
confidence: 99%